Analyzing the Element of Spirituality Manifest in the Texts of “Waiting for Godot” and “Forty Rules of Love”: A Study Based on Van Dijk’s Micro Structural Analysis - Muhammad Waseem; Zahra Khan; Qurat Ul ain (Indus Journal of Social Sciences, 2025)
This research article examines a comparative analysis of Samuel Beckett’s Waiting for Godot and Elif Shafak’s The Forty Rules of Love using Van Dijk’s model of textuality, under the lens of microstructure. This study investigates the dialogues and structure of both texts, analyzing how their micro-level elements, such as coherence, cohesion, and different devices contribute to convey spiritual expressions. While "Waiting for Godot” shows spiritual despair and human condition through incomplete dialogues and settings, The “Forty Rules of Love” explores deep conversation and narrative to highlight spirituality, and self-discovery. The analysis reveals how these seemingly disparate texts, rooted in different traditions, modernism and Sufi spirituality intersect on the basic human quest for meaning. By applying Van Dijk’s model (1970s), the research examines the textual components that shape the reader’s understanding of the work that presents deeper and spiritual questions. The result indicates that spirituality creates impact on “Waiting for Godot” and “Forty Rules of Love” on the basis of how both texts, regarding their context and dialogues differences, suggests deep observation of power of spirituality for the search of meaning, ultimately bridging the gap between self-discovery and spiritual analysis. This study demonstrates to understand intertextual connections with the help of spirituality.